Bridging the Divide: Measuring Party System Change and Classifying Party Systems - Riccardo Pelizzo; Zim Nwokora (African Governance and Development Institute (AGDI), 2016)
Party systems research has proceeded along two parallel lines of inquiry, one predominantly “qualitative” and the other “quantitative.” This article attempts to bridge this divide in two ways. First, by showing that qualitative information can be valuable in the construction of quantitative measures. Second, by showing that the results from applying theoretically- sensitive measurement tools can be useful for qualitative classification. These analyses are performed using an original dataset of party system changes in Sub-Saharan Africa.
Keywords: K00; O10; P16; P43; P50; 330; Political Parties; Political Institutions; Party System Change